2015
DOI: 10.1016/j.matchemphys.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide and zinc hydroxide formation via aqueous precipitation: Effect of the preparation route and lysozyme addition

Abstract: h i g h l i g h t s g r a p h i c a l a b s t r a c tAqueous precipitation products of Zn(NO 3 ) 2 and NaOH were prepared. Synthesis route and lysozyme addition affected morphology of the products. Aqueous precipitation products of Zn(NO 3 ) 2 and NaOH obtained by changing the method of combining the reactants and by using lysozyme as an additive were investigated. In the case of single addition method, octahedral ε-Zn(OH) 2 and plate-like b-Zn(OH) 2 structures formed in the absence and in the presence of lyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…We use the acetonitrile solvent system for MAPbI 3 , as this provides high‐crystallinity films, as cast at room temperature, allowing for initial inspection of the interface with minimal thermally induced effects . We assign the peaks at 3138 and 3179 cm −1 (Figure d) to symmetric and asymmetric stretching of NH 3 + , and the broad band around 3485 cm −1 to O–H stretching from hydroxyl groups (or physically adsorbed water) . Additional annealing results in gradual accumulation of hydroxyl groups and the loss of CH 3 NH 3 + to volatile CH 3 NH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We use the acetonitrile solvent system for MAPbI 3 , as this provides high‐crystallinity films, as cast at room temperature, allowing for initial inspection of the interface with minimal thermally induced effects . We assign the peaks at 3138 and 3179 cm −1 (Figure d) to symmetric and asymmetric stretching of NH 3 + , and the broad band around 3485 cm −1 to O–H stretching from hydroxyl groups (or physically adsorbed water) . Additional annealing results in gradual accumulation of hydroxyl groups and the loss of CH 3 NH 3 + to volatile CH 3 NH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Their formation has been observed at lower pH, namely Zn(OH) 2 at ca. 6 pH and ZnO at 9 pH . During the synthesis of Zn(OH) 2 , NaOH was added dropwise to achieve a pH equal to 8 to obtain the solid form of Zn(OH) 2 (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption band at 480 cm −1 is assigned to the stretching vibration of the Zn−O lattice . The band observed at 927 cm −1 results from asymmetric stretching vibrations of Zn‐O−Zn bridge oxygens in the structure . Two bands observed at ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was, due to the availability of more nucleating sites offered by MMT matrix. TEM results showed that the Ag and ZnO NPs formed during the reduction of Ag + and Zn 2+ ions in the urtica leaf extract are more uniform than other chemical and biosynthesis methods [30].…”
Section: Electron Microscopy Studymentioning
confidence: 85%